Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
0
Step-by-step explanation:
Assuming the problem is:
"lim x-> 4 f(x)=5 lim x-> 4 g(x)=0 and lim x-> 4 h(x)=-2, then find lim x->4 (fg)(x)"
lim x->4 (fg)(x)
Since we know the limits of f and g at x=4 exist we can write the limit as:
lim x->4 f(x) lim x->4 g(x) (since fg(x) means f times g of x.)
5(0)
0
if lim x-> 4 f(x)=5 lim x-> 4 f g(x)=0 and lim x-> 4 f h(x)=-2, then lim (fg)(x) 0
What is inequality?
inequality the relationship between two expressions that are not equal, employing a sign such as ≠ “not equal to,” > “greater than,” or < “less than.”.
Assuming the problem is:
"lim x-> 4 f(x)=5 lim x-> 4 g(x)=0 and lim x-> 4 h(x)=-2, then find lim x->4 (fg)(x)"
lim x->4 (fg)(x)
Since we know the limits of f and g at x=4 exist we can write the limit as:
lim x->4 f(x) lim x->4 g(x) (since fg(x) means f times g of x.)
=5(0)
=0
Hence the lim x-> 4 f(x)=5 lim x-> 4 f g(x)=0 and lim x-> 4 f h(x)=-2, then lim (fg)(x) 0
To know more about inequality follow
https://brainly.com/question/24372553
#SPJ2
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.